2018
DOI: 10.1039/c7em00549k
|View full text |Cite
|
Sign up to set email alerts
|

Temporal trends of halogenated flame retardants in the atmosphere of the Canadian Great Lakes Basin (2005–2014)

Abstract: Organic pollutants have been monitored in the atmosphere of the Great Lake Basin (GLB) since the 1990s in support of the Canada-US Great Lakes Water Quality Agreement and to determine the effectiveness of source reduction measures and factors influencing air concentrations. Air samples were collected between 2005 and 2014 at three sites with different geographical characteristics (Burnt Island, Egbert and Point Petre) in the Canadian GLB using high-volume air samplers and the air samples were analyzed for poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 50 publications
2
17
0
Order By: Relevance
“…The BDE profiles from 2015-17 are similar to those found in the same population of grey seals from the late 1990s and in 2008 (Kalantzi, Hall, Thomas, & Jones, 2005;Vanden Berghe et al, 2012), found in the blubber from grey seals elsewhere (Ikonomou & Addison, 2008), and reported in recent studies on other marine mammals (Bjurlid, Dam, et al, 2018;Ochiai et al, 2017;Ramu, Kajiwara, Tanabe, Lam, & Jefferson, 2005;Rigét et al, 2006;Ross et al, 2013;Weijs, Dirtu, et al, 2009) of BDEs (Airaksinen et al, 2014;Bjurlid, Dam, et al, 2018;Bjurlid, Roos, et al, 2018;Houde et al, 2017;Rigét et al, 2006Rigét et al, , 2019Ross et al, 2013;Sanganyado, Rajput, & Liu, 2018;Shunthirasingham et al, 2018), and may have stabilized recently in some regions (Brown, MacDonald, Muir, & Letcher, 2018;Fernandes et al, 2018;Houde et al, 2017;Rigét et al, 2016Rigét et al, , 2019. In combination with the technical disparities discussed below, the BDE data here do not provide a sufficient recent time series to determine whether the bans have been effective at reducing BDEs in grey seal blubber, but provide a starting point for future studies or comparisons to investigate the efficacy of the ban and its impact on levels in top predators.…”
Section: Bde Profiles and Concentrationssupporting
confidence: 83%
See 1 more Smart Citation
“…The BDE profiles from 2015-17 are similar to those found in the same population of grey seals from the late 1990s and in 2008 (Kalantzi, Hall, Thomas, & Jones, 2005;Vanden Berghe et al, 2012), found in the blubber from grey seals elsewhere (Ikonomou & Addison, 2008), and reported in recent studies on other marine mammals (Bjurlid, Dam, et al, 2018;Ochiai et al, 2017;Ramu, Kajiwara, Tanabe, Lam, & Jefferson, 2005;Rigét et al, 2006;Ross et al, 2013;Weijs, Dirtu, et al, 2009) of BDEs (Airaksinen et al, 2014;Bjurlid, Dam, et al, 2018;Bjurlid, Roos, et al, 2018;Houde et al, 2017;Rigét et al, 2006Rigét et al, , 2019Ross et al, 2013;Sanganyado, Rajput, & Liu, 2018;Shunthirasingham et al, 2018), and may have stabilized recently in some regions (Brown, MacDonald, Muir, & Letcher, 2018;Fernandes et al, 2018;Houde et al, 2017;Rigét et al, 2016Rigét et al, , 2019. In combination with the technical disparities discussed below, the BDE data here do not provide a sufficient recent time series to determine whether the bans have been effective at reducing BDEs in grey seal blubber, but provide a starting point for future studies or comparisons to investigate the efficacy of the ban and its impact on levels in top predators.…”
Section: Bde Profiles and Concentrationssupporting
confidence: 83%
“…Recent BDE values here are 10-20-fold lower than the levels reported in adult harbour seals from the North Sea from 1999 to 2004 (Weijs, Dirtu, et al, 2009), and are an order of magnitude lower than values reported in UK grey seal pup blubber from 1998 to 2000 (Kalantzi et al, 2005), and in Salish Sea harbour seal pup blubber from 1984 to 2009 (Ross et al, 2013). Findings from other studies in the marine environment globally suggest that BDE levels peaked in the early 2000s and then fell, as a result of the ban on penta-and tetra-mixes of BDEs (Airaksinen et al, 2014;Bjurlid, Dam, et al, 2018;Bjurlid, Roos, et al, 2018;Houde et al, 2017;Rigét et al, 2006Rigét et al, , 2019Ross et al, 2013;Sanganyado, Rajput, & Liu, 2018;Shunthirasingham et al, 2018), and may have stabilized recently in some regions (Brown, MacDonald, Muir, & Letcher, 2018;Fernandes et al, 2018;Houde et al, 2017;Rigét et al, 2016Rigét et al, , 2019. In combination with the technical disparities discussed below, the BDE data here do not provide a sufficient recent time series to determine whether the bans have been effective at reducing BDEs in grey seal blubber, but provide a starting point for future studies or comparisons to investigate the efficacy of the ban and its impact on levels in top predators.…”
Section: Bde Profiles and Concentrationsmentioning
confidence: 71%
“…It should be noted that this decreasing trend of ∑DP in the GAPS samples is in contrast to increasing trends observed at background sites in the Great Lakes for DP in air over the period of 2005−2013 by Liu et al 30 Shunthirasingham et al reported decreasing trends for anti-DP in the Canadian Great Lakes basin between 2005 and 2014, while syn-DP trends were not consistent between sampling sites. 39 Ongoing analysis of GAPS samples in the future will provide further insight into temporal trends for DP in air at the global scale and in relation to global emissions, which were recently modeled by Hansen et al 40 In addition to DP, the GAPS samples from this study were screened for a long list of novel FRs, which are not discussed further because most were present at levels that were below detection limits. This outcome for the novel FRs highlights a growing problem with detection issues in ambient air for an expanding and diverse set of FR chemicals that are increasingly being used in commercial products as replacements for the now globally regulated PBDEs, which were once the most widely used class of FRs.…”
Section: ■ Materials and Methodsmentioning
confidence: 94%
“…Given that the technical deca mixture represents 83 % of the global PBDE market (in 2001; Besis and Samara, 2012), these distributions suggest that either lower congeners are more prone to volatilization from products or from other environmental media compared to the higher brominated congeners or that photolytic degradation of BDE209 to lower brominated BDEs is occurring (Luo et al, 2014). Indeed, an increase of lower brominated congeners (hexa through nona) was observed under photolysis of BDE209 in solvents, sediments, soils and sands (Eriksson et al, 2004;Söderström et al, 2004). However, photolysis is not specific to BDE209, but relevant for all congeners, such as BDE99 (formation of BDE47; Fang et al, 2008;Sanchez-Prado et al, 2005).…”
Section: Pbde Concentration Levelsmentioning
confidence: 99%